A copper nitride catalyst for the efficient hydroxylation of aryl halides under ligand-free conditions. Issue 30 (21st May 2021) - Xu, Hang; Yamaguchi, Sho; Mitsudome, Takato; Mizugaki, Tomoo
Abstract : Reusable copper nitride nanoparticles enable ligand-free, heterogeneous, and high-yield catalytic hydroxylation of a broad range of aryl halides with excellent substrate tolerance under mild reaction conditions. Abstract : Copper nitride (Cu3 N) was used as a heterogeneous catalyst for the hydroxylation of aryl halides under ligand-free conditions. The cubic Cu3 N nanoparticles showed high catalytic activity, comparable to those of conventional Cu catalysts with nitrogen ligands, demonstrating that the nitrogen atoms in Cu3 N act as functional ligands that promote hydroxylation.